2017
DOI: 10.1017/mor.2017.46
|View full text |Cite
|
Sign up to set email alerts
|

Technological Innovation Research in China and India: A Bibliometric Analysis for the Period 1991–2015

Abstract: Although a substantial literature on the management of technological innovation exists, several scholars argue that much of this research has been rooted in Western contexts, where key assumptions are very different from those in emerging economies. Building on this viewpoint, we investigate the current state of knowledge on technological innovation in two of the largest and fastest growing emerging economies: China and India. We undertook a bibliometric analysis of author keywords and combined different quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 269 publications
2
49
0
Order By: Relevance
“…The primary contribution is to the literature on entrepreneurship and innovation in emerging markets (Ahmed et al, 2005;Yamakawa et al, 2013;Chatterjee and Sahasranamam, 2014;Bruton and Chen, 2016;Sahasranamam and Sud, 2016). It also extends the literature on the role of property rights protection in state-controlled economies Hendrischke, 2003, 2008;Li, 2004;Schmiele, 2013;Marcotte, 2014;Chatterjee and Sahasranamam, 2018). This study observes that in economies undergoing an institutional transition, such as China, there is a strong disincentive for individuals to invest their human and financial capital towards starting a new venture in the absence of legislation offering property rights protection.…”
Section: Contributionssupporting
confidence: 73%
“…The primary contribution is to the literature on entrepreneurship and innovation in emerging markets (Ahmed et al, 2005;Yamakawa et al, 2013;Chatterjee and Sahasranamam, 2014;Bruton and Chen, 2016;Sahasranamam and Sud, 2016). It also extends the literature on the role of property rights protection in state-controlled economies Hendrischke, 2003, 2008;Li, 2004;Schmiele, 2013;Marcotte, 2014;Chatterjee and Sahasranamam, 2018). This study observes that in economies undergoing an institutional transition, such as China, there is a strong disincentive for individuals to invest their human and financial capital towards starting a new venture in the absence of legislation offering property rights protection.…”
Section: Contributionssupporting
confidence: 73%
“…Hence, future research could explore the role of sub-national institutions on social entrepreneurship. There is also need for greater quantitative research to study how social entrepreneurship emerges and thrives in contexts of formal institutional voids (Chatterjee & Sahasranamam, 2018;Mair, Martí, & Ventresca, 2012). Despite these limitations, our study does provide an understanding of how individual capital and formal institutional context interact to influence social entrepreneurship entry.…”
Section: Limitations Future Research and Conclusionmentioning
confidence: 95%
“…Whatever happens, there is enormous potential for global strategy researchers to advance extant understanding of innovation in and from India. A recent bibliometric analysis of management research on China and India for the period 1991–2015 found 130 articles on China but only 32 on India (Chatterjee & Sahasranamam, forthcoming). Their finding echoes Nair et al (), who lament the dearth of research on innovation in India.…”
Section: The Future Of Innovation In Indiamentioning
confidence: 99%